2016
DOI: 10.1002/brb3.516
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of inflammatory leukocyte markers during intravenous immunoglobulin treatment associated with clinical efficacy in chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: ObjectiveThe objective of the study was to profile leukocyte markers modulated during intravenous immunoglobulin (IVIg) treatment, and to identify markers and immune pathways associated with clinical efficacy of IVIg for chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) with potential for monitoring treatment efficacy.MethodsResponse to IVIg treatment in newly diagnosed IVIg‐naïve and established IVIg‐experienced patients was assessed by changes in expression of inflammatory leukocyte markers by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
4
9
0
Order By: Relevance
“…An effect of IVIG that was common to multiple NK cell and T cell subsets was an increase in the frequency of cells expressing CD62L in vivo, which largely occurred in KD patients (Figure 4). This has been previously demonstrated in human myeloid DCs (46) and murine CD8 + T cells (47), and does not appear to occur when IVIG is administered at low doses (24). CD62L is an important adhesion molecule involved in trafficking from the blood into lymphoid tissues [reviewed in (48)].…”
Section: Discussionmentioning
confidence: 98%
“…An effect of IVIG that was common to multiple NK cell and T cell subsets was an increase in the frequency of cells expressing CD62L in vivo, which largely occurred in KD patients (Figure 4). This has been previously demonstrated in human myeloid DCs (46) and murine CD8 + T cells (47), and does not appear to occur when IVIG is administered at low doses (24). CD62L is an important adhesion molecule involved in trafficking from the blood into lymphoid tissues [reviewed in (48)].…”
Section: Discussionmentioning
confidence: 98%
“…Additional mechanisms, such as apoptosis or other cell death pathways, may also be involved, and we cannot exclude an effect of the IVIG treatment, as reported previously in some studies. 23,27,28,30,31 Compared with children with acute infection, most of the individuals with postacute hyperinflammation received IVIG treatment before sampling, some combined with glucocorticosteroids. The immunosuppressive effects of glucocorticoids are identified at the cytokine/chemokine level.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, in some cases, IVIG treatment could impair DC function and decrease monocyte and DC proportions. 23,25,[27][28][29][30][31] In addition, some heterogeneity was observed in the proportions of non-classical monocytes in Acute-Inf (CoV-2 + ) cases and additional heterogeneity in the proportions of classical and intermediate monocytes in individuals with severe myocarditis (MIS-C_MYO (CoV-2 + )) (Figures 3A and 3B), but there was no correlation with clinical data, including treatments, age (Table S1), and cytokine/chemokine measurements (Figures 2 and S2). Additional modifications were detected in individuals with acute SARS-CoV-2 infection (Acute-Inf (CoV-2 + ) cases), consisting of a decrease in mucosal-associated invariant T cells (MAIT) and an excess of naive and central memory CD4 + T cells (Figures 3A, 3B, S3C, and S3D).…”
Section: Low Monocyte and Dendritic Cell Frequencies In Individuals With Postacute Hyperinflammatory Illnessmentioning
confidence: 99%
“…Over the last years, several studies tried to establish markers of peripheral blood mononuclear cells (PBMC) and serum cytokines that might reflect disease activity in CIDP. Of those, reduced numbers of CD32b expressing memory B cells and monocytes, as well as increased numbers of CD16 + myeloid dendritic cells, were associated with disease activity and/or poor response to immunoglobulin therapy (Tackenberg et al 2009;Dyer et al 2016). Other studies demonstrated that CIDP is associated with a reduction of regulatory T cells, as well as with an increase of monocytes (Matà et al 2007;Sanvito et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of IVIg on CD32b expression are time-dependent. Whereas one week after IVIg infusion, CD32b expression decreases on B cells and monocytes due to IVIg-induced receptor internalization (Bouhlal et al 2014;Dyer et al 2016), Tackenberg and colleagues demonstrated that CD32b expression on these cells increases two to three weeks afterward (Tackenberg et al 2009). Furthermore, IVIg suppresses pro-inflammatory myeloid dendritic cells and their pro-inflammatory CD32a (FcγRIIa) receptors (Boruchov et al 2005;Dyer et al 2016).…”
Section: Introductionmentioning
confidence: 99%